Advanced electrochromic/electrofluorochromic poly(amic acid) toward the colorimetric/fluorometric dual-determination of glycosuria. (August 2021) - Zhang, Y.; Li, Y.; Jia, X.; Berda, E.B.; Wang, C.; Chao, D.
Abstract: The electrochromic/electrofluorochromic (EC/EFC) dual-functional polymers have gained intense attention owing to the unique electrochemically induced absorption and emission change simultaneously. Most of the efforts have recently been devoted to improving their EC/EFC performance. However, the practical application studies of the EC/EFC polymers are still in their infancy. Herein, we present a poly(amic acid) based material bearing high solid fluorescence-efficiency AIEgens and electroactive oligoaniline groups, featuring a good electrochromic performance with desirable optical contrast, high coloration efficiency, and outstanding durability. This occurs in tandem with electrofluorochromic behavior with ideal fluorescence contrast and moderate switching speed. By virtue of the versatile electrospinning technique, we manufactured a nanofibrous test strip base on the resultant polymer for glucose determination. The colorimetric/fluorometric dual-determination of glucose is carried out with an obvious color change from gray to dark green, along with a drastic fluorescence change from light to dark, which exhibits numerous advantages of easy operation, rapid detection, favorable selectivity, and unique repeated use feature. Furthermore, the nanofibrous test strips also provide reliable results in the glycosuria test. This strategy shows distinct promise for future sensing applications. Highlights: A new electrochromic/electrofluorochromic dual-functional polymer was synthesized. The resultant polymer bearing AIE groups and electroactive oligoaniline segments. A nanofibrous test strip is manufactured for glucosuria determination. A smart colorimetric/fluorometric dual-determination of glucosuria is carried out.